2017
DOI: 10.1111/cas.13332
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6/STAT3 signaling as a promising target to improve the efficacy of cancer immunotherapy

Abstract: Overcoming the immunosuppressive state in tumor microenvironments is a critical issue for improving the efficacy of cancer immunotherapy. Interleukin (IL)‐6, a pleiotropic cytokine, is highly produced in the tumor‐bearing host. Previous studies have indicated that IL‐6 suppresses the antigen presentation ability of dendritic cells (DC) through activation of signal transducer and activator of transcription 3 (STAT3). Thus, we focused on the precise effect of the IL‐6/STAT3 signaling cascade on human DC and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
144
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(147 citation statements)
references
References 72 publications
(147 reference statements)
1
144
0
2
Order By: Relevance
“…In total, the network had 2684 links with 343 ceRNA interactions, 20 miRNA‐ LINC00472 regulations, 1 TF‐ LINC00472 regulatory relationship, 3 RBPs interacting with LINC00472 and 2318 PPIs among these proteins (Figure , Table S3). In the regulatory network, the TF was signal transducer and activator of transcription‐3, which had been reported to be involved in many types of cancer . Three RNA‐binding proteins are heterogeneous nuclear ribonucleoprotein A1 ( HNRNPA1 ), heterogeneous nuclear ribonucleoprotein H1 ( HNRNPH1 ) and fused‐in‐sarcoma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, the network had 2684 links with 343 ceRNA interactions, 20 miRNA‐ LINC00472 regulations, 1 TF‐ LINC00472 regulatory relationship, 3 RBPs interacting with LINC00472 and 2318 PPIs among these proteins (Figure , Table S3). In the regulatory network, the TF was signal transducer and activator of transcription‐3, which had been reported to be involved in many types of cancer . Three RNA‐binding proteins are heterogeneous nuclear ribonucleoprotein A1 ( HNRNPA1 ), heterogeneous nuclear ribonucleoprotein H1 ( HNRNPH1 ) and fused‐in‐sarcoma.…”
Section: Resultsmentioning
confidence: 99%
“…In the regulatory network, the TF was signal transducer and activator of transcription-3, which had been reported to be involved in many types of cancer. 35 Three RNA-binding proteins are heterogeneous nuclear ribonucleoprotein A1 (HNRNPA1), heterogeneous nuclear ribonucleoprotein H1 (HNRNPH1) and fused-in-sarcoma. HNRNPA1 expression level was higher in low-stage CRC compared with that of high-stage CRC, 36 while HNRNPH1 was downregulated in CRC.…”
Section: Functional Annotation and Regulatory Network Of Linc00472mentioning
confidence: 99%
“…10 As expected, our study found that IL-6 promoted TIM-4 expression in NSCLC cell lines via NF-κB pathway. In addition to NF-κB, STAT3 is another key factor in IL-6 signalling pathway, 34,35 and it has been documented that IL-6 promoted lung cancer development and progression by activating STAT3. 36,37 Another study found that IL-6 could induce immunosuppressive factor PD-L1 expression on peripheral myeloid cells through STAT3-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in dendritic cells (DC) histone deacetylation is crucial for differentiation (Nencioni et al, 2007). Also, the TF signal transducer and activator of transcription 3 (STAT3) controls dendritic function by regulating target genes involved in DC differentiation, such as the IDO enzyme and the HLA class II genes (Sun et al, 2009;Cacalano, 2016;Kitamura et al, 2017). Importantly, the circadian HDAC SIRT1 is a master regulator of STAT3 function by deacetylation, hereby inactivating it (Nie et al, 2009) (Figure 2).…”
Section: The Adaptive Immune System and The Circadian Clock: An Epigementioning
confidence: 99%